Role of hepatitis B surface antibody in seroreversion of hepatitis B surface antigen in patients achieving hepatitis B surface antigen loss with pegylated interferon‐based therapy. Issue 10 (13th August 2022) - Gao, Na; Yu, Huiying; Zhang, Jing; Mo, Zhishuo; Chu, Junhao; Xie, Chan; Peng, Liang; Gao, Zhiliang
Abstract: It is unclear whether hepatitis B surface antibody (HBsAb) confers clinical benefits after HBsAg seroclearance, especially in hepatitis B surface antigen (HBsAg) seroreversion and maintenance of HBsAb. We evaluated this in patients ( n  = 222) with HBsAg loss following treatment with pegylated interferon (PEG‐IFN)‐based therapy who completed a 48‐week follow‐up period. Serum hepatitis B virus (HBV) markers and biochemical indicators were evaluated every 3 months. The primary endpoint was HBsAg seroreversion. Factors associated with HBsAg seroreversion were also investigated. HBsAb ≥100 mIU/ml resulted in a lower HBsAg seroreversion rate than an HBsAb‐negative status (5.5% vs. 29.5%, p  < .001); however, the seroreversion rate was not significantly different between patients with HBsAb 10–100 mIU/ml and those in the HBsAb‐negative group. Patients with HBsAb ≥100 mIU/ml had a lower HBsAb loss rate than those with HBsAb 10–100 mIU/ml (7.3% vs. 21.7%, p  = .005). The final HBsAg seroreversion and HBV DNA relapse rates were 13.5% and 1.8%, respectively. HBsAb ≥100 mIU/ml at the off‐treatment time (odds ratio [OR] 0.110, 95% confidence interval [CI]: 0.034–0.353, p  < .001) and treatment time to attain HBsAg loss >28 weeks (OR 2.508, 95% CI: 1.068–5.890, p  = .035) were predictors of HBsAg seroreversion. Consolidation therapy for 12–24 weeks resulted in higher HBsAb titres than consolidation therapy for ≤12 weeks in HBsAb‐negative patients at the off‐treatment time ( p  < .001). HBsAg seroconversion with HBsAb ≥100 mIU/ml decreases HBsAg seroreversion and provides an efficient maintenance rate of HBsAb. HBsAg seroconversion with high HBsAb titres may be clinically beneficial for chronic hepatitis B treated with PEG‐IFN‐based therapy.